Living in two neighborhoods: Social interaction effects in the lab - Armin Falk; Urs Fischbacher; Simon Gächter (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2009)
Field evidence suggests that people belonging to the same group often behave similarly, i.e., behavior exhibits social interaction effects. We conduct a laboratory experiment that avoids the identification problem present in the field and allows us to study the behavioral logic of social interaction effects. Our novel design feature is that each subject is simultaneously a member of two randomly assigned and identical groups where only members ('neighbors') are different. We study behavior in a coordination game with multiple equilibria and a public goods game, which has only one equilibrium in material payoffs. We speak of social interactions if the same subject at the same time makes group-specific decisions that depend on their respective neighbors' decisions. We find that a majority of subjects exhibits social interaction effects both when the game has multiple equilibria in material payoffs and when it only has one equilibrium.
Keywords: C91; H41; K42; H26; 330; social interactions; identification; experiments; coordination; cooperation; Nachbarschaftsökonomie; Öffentliches Gut; Test; Theorie